Financial Education or Incentivizing Learning-by-Doing? Evidence from an RCT with Undergraduate Students - Luis Oberrauch; Tim Kaiser (CESifo GmbH, 2024)
We study the effects of digital financial education interventions on undergraduate students' financial knowledge in a small-scale RCT. We test the substitutability or complementarity of two treatments: an online video financial education treatment and an incentive-based approach where students are issued pre-paid voucher cards worth 50 EUR to register with a broker specializing in robo-advised investment in Exchange Traded Funds (ETFs). Three months after the intervention, the video treatment enhanced financial knowledge scores by more than 0.5 standard deviations. Conversely, the vouchers showed no effect. The findings suggest that subsidies encouraging robo-advised investment into ETFs cannot substitute direct financial education in our setting, and there is no evidence for complementarity between these interventions.
Keywords: G53; 330; digital intervention; financial literacy; Financial knowledge; financial education; robo-advisor; ETFs